Mesenchymal stem cell derived exosomes - Tang, Yaoliang; Dawn, Buddhadeb (London Elsevier, 2015)
"Mesenchymal stem cell-derived exosomes are at the forefront of research in two of the most high profile and funded scientific areas--cardiovascular research and stem cells. Mesenchymal Stem Cell Derived Exosomes provides insight into the biofunction and molecular mechanisms, practical tools for research, and looks toward the clinical applications of this exciting phenomenon, which is emerging as an effective diagnostic technique. Primarily focused on the cardiovascular applications where there have been the greatest advancements toward the clinic, this is the first compendium for clinical and biomedical researchers who are interested in integrating MSC-derived exosomes as a diagnostic and therapeutic tool."--
Insights into the Mechanism of Exosome Formation and Secretion / Kobina Essandoh, Guo-Chang Fan -- An Overview of the Proteomic and miRNA Cargo in MSC-Derived Exosomes / Soon Sim Tan, Tian Sheng Chen, Kok Hian Tan, Sai Kiang Lim -- Exosome Function in miRNA-Mediated Paracrine Effects / Sathyamoorthy Balasubramanian, Sheeja Rajasingh, Jayakumar Thangavel, Buddhadeb Dawn, Johnson Rajasingh -- Current Methods to Purify and Characterize Exosomes / W. Michael Dismuke, Yutao Liu -- Stem Cell Extracellular Vesicles: A Novel Cell-Based Therapy for Cardiovascular Diseases / Ewa K. Zuba-Surma, Marta Adamiak, Buddhadeb Dawn -- Therapeutic Potential of Stem Cell-Derived Extracellular Vesicles in Cardioprotection and Myocardium Repair / Bin Yu, Muhammad Ashraf, Meifeng Xu -- Engineered/Hypoxia-Preconditioned MSC-Derived Exosome: Its Potential Therapeutic Applications / Wei Zhu, Han Chen, Jian'an Wang -- Exosome-Based Translational Nanomedicine: The Therapeutic Potential for Drug Delivery / Lei Lv, Qingtan Zeng, Shenjun Wu, Hui Xie, Jiaquan Chen, Xiang Jiang Guo, Changning Hao, Xue Zhang, Meng Ye, Lan Zhang -- Effect of Exosomes from Mesenchymal Stem Cells on Angiogenesis / Susmita Sahoo, Feng Dong, Lola DiVincenzo, William Chilian, Liya Yin -- Exosomes for Bone Diseases / Paulomi Sanghavi, Porter Young, Sunil Upadhyay, Mark W. Hamrick -- Diagnostic and Prognostic Applications of MicroRNA-Abundant Circulating Exosomes / Baron Arnone, Xiaoqi Zhao, Zhipeng Zou, Gangjian Qin, Min Cheng.
Keywords: Mesenchymal stem cells; Nanomedicine; Mesenchymal Stromal Cells; Exosomes; Nanomedicine; Cardiovascular Diseases; Mesenchymal stem cells; Nanomedicine